Dogged by death - Scott, Laura, 1961- (Scott, Laura, 1961- Furry friends mystery., 2021)
After losing her fiancé, her clinic, and all her savings, veterinarian Ally Winter moves back to Willow Bluff, Wisconsin and becomes accidentally involved when a sleazy lawyer is murdered in his home office with his Boxer the only witness.